How to support innovative small firms? Bibliometric analysis and visualization of start-up incubation - Domicián Máté; Ni Made Estiyanti; Adam Novotny (Journal of Innovation and Entrepreneurship, 2024)
Supporting the birth and development of innovative small firms, i.e., start-up incubation, has emerged as a critical factor in fostering entrepreneurship, innovation, regional development, and more recently, sustainability. This bibliometric review aims to comprehensively understand and visualize different research perspectives on how start-ups are successfully incubated. A total of 1116 Scopus articles were selected and synthesized using a qualitative approach. The study applies novel visualization techniques (Citation Network Analysis, Global Citation Score, Burst Detection Analysis and Co-Occurrence Networks of Keywords) to map the scientific structure of start-up incubation research, including the clusters of the leading research topics based on citation networks, the most cited articles, and the keywords with the most substantial citation bursts as well as their co-occurrence. We evaluate research on start-up incubation from 1972 to 2023 and show how the topic has advanced by scholars' changing interests over time. We identify five clusters that reflect distinct study themes and their most cited references. The findings contribute to a more comprehensive understanding of the evolution of start-up incubation research, which developed from a focus on biotechnology and technology transfer toward the current research trends on accelerators and (entrepreneurial) ecosystems. This paper also provides insights for policymakers and start-up incubation managers to make informed decisions.
Keywords: M13; O31; O32; O38; 650; Bibliometric analysis; Incubation; Start-up; Visualization analysis